Population genetic structure of two herds of Aberdeen Angus cattle breed in Colombia (2021)
ABSTRACT: Background: Two biotypes of Aberdeen Angus cattle breed, known as Old Type and New Type, that differ in their origin and beef production are formally recognized. In Colombia, this breed has been commercialized for approximately 80 years. Studies on the origin, kinship and levels of genetic diversity of this breed in Colombian herds are scarce, yet important for planning crossing and management strategies. Objective: To measure the genetic diversity and structure of two Colombian herds of Old Type and New Type biotypes of Aberdeen Angus from Huila and Cundinamarca provinces and assess mitochondrial introgression with other breeds. Methods: A set of ten microsatellites and sequences of the Mitochondrial Control Region were characterized. Estimators of genetic diversity and population differentiation along with tests of population assignment were applied. Results: Nuclear loci were highly polymorphic as shown by the Polymorphic Information Content (0.599) and the Probability of Identity (1.896 10-08). Both populations were highly diverse and clearly differentiated into two groups corresponding to the Old Type and New Type phenotypes. In contrast, mitochondrial data failed to distinguish these two groups and showed extensive admixture. Conclusions: This study optimized a set of ten highly polymorphic nuclear markers that may be used for parentage and population genetic studies of Aberdeen Angus. Genetic differentiation in these loci agreed with phenotypic differences of the Old and New Types. However, mitochondrial data indicated ancestry of multiple European breeds in the origin of Colombian Aberdeen Angus.